Dab1 contributes differently to the morphogenesis of the hippocampal subdivisions. (25th September 2017) - Blume, Marissa; Inoguchi, Fuduki; Sugiyama, Taku; Owada, Yuji; Osumi, Noriko; Aimi, Yoshinari; Taki, Kosuke; Katsuyama, Yu
Abstract : The hippocampal formation (HF) is morphologically and functionally distinguishable into the subdivisions, such as the dentate gyrus (DG), subiculum, and Ammon's horn. The Ammon's horn is further divided into the CA (Cornu Ammonis)1, CA2, and CA3. The Reelin‐Dab1 signal is essential for the morphogenesis of the mammalian brain. In the neocortex of Reelin‐Dab1 signal mutants the laminar pattern of the neurons is disrupted along the radial axis. Morphological abnormalities in the HF of the Reelin‐Dab1 mutants were known, but how these abnormalities appear during development had not been extensively studied. We examined the morphology of the well‐developed Dab1 deficient HF by staining with a silver impregnation method in this report, and found that disruption of lamination in the CA1, CA3, and DG was different. Abnormalities observed in the development of Dab1 deficient CA1 were similar to those reported in the neocortical development, while Dab1 deficient CA3 neuronal progenitors radially spreaded beyond presumptive pyramidal layer. The intermediate progenitor cells ectopically located in the Dab1 deficient DG, but neurogenesis was normal in the CA1 and CA3. These observations suggest that the morphogenesis in these HF subdivisions employs different developmental mechanisms involving Dab1 function. Abstract : By detailed observations of developmental process of the hippocampal formation in Dab1 deficient mice, it was found that morphogenesis in the CA1, CA3, and dentate gyrus in the mutant was differently affected by Dab1 deficiency, suggesting that Dab1 is involved in these hipocampla subdivisions collaborating with different developmental mechanisms.